Radiation therapy is an important factor to improve survival in pediatric patients with head and neck rhabdomyosarcoma by enhancing local control: a historical cohort study from a single center - Wen, Yuan; Huang, Dongsheng; Zhang, Weiling; Zhang, Yi; Hu, Huimin; Li, Jing (BMC pediatrics, 2020)
The purpose of this study is to analyze the influence of radiation therapy on survival in a historical cohort of 56 pediatric patients with head and neck rhabdomyosarcoma. A historical cohort of 56 pediatric patients with head and neck rhabdomyosarcoma from June 1st, 2013 to June 30th, 2019 was chosen. Clinical data and follow up results were collected including all diagnosis, treatment and prognosis information. Overall survival (OS) and event free survival (EFS) as time-to-event distributions were estimated with Kaplan-Meier method, and univariate analysis was performed with log rank test to detect differences between groups. Multivariate analysis was performed to explore the risk factors for survival with Cox proportional hazard model. The media follow up time of all 56 patients was 31.8 months (range 3.5-74.6 months). There were 26 events during follow up, including 14 disease progressions and 12 relapses. The estimated 5-year OS of all patients was 69.9%, and the estimated 5-year EFS was 48.8%. Patients with radiation therapy as a component of the initial treatment plan had better 5-year OS and EFS compared with those without radiation therapy (OS 80.3% vs. 49.7%, p = 0.003 and EFS 63.9% vs. 21.9%, p < 0.001). In patients with events, those who received salvage radiation therapy had better 5-year OS compared with those who didn't (OS 66.0% vs. 31.2%, p = 0.033). On multivariate analysis, tumor size > 5 cm and non-initial radiation therapy were independent risk factors for OS in all patients, non-initial radiation therapy was an independent risk factor for EFS in all patients, and tumor size > 5 cm was an independent risk factor for OS in patients with events. Radiation therapy as a component of initial treatment can improve the OS and EFS in pediatric head and neck rhabdomyosarcoma patients by enhancing local control, and non-initial radiation therapy is an independent risk factor for OS and EFS. Salvage radiation therapy still can improve OS in patients with disease progression and relapse. Tumor size > 5 cm is an independent risk factor for OS in pediatric HNRMS patients with or without disease progression/relapse.